The Factors Motivating Voluntary Disclosure of Carbon Information: Evidence Based on Italian Listed Companies. (June 2018) - Jaggi, Bikki; Allini, Alessandra; Macchioni, Riccardo; Zagaria, Claudia
The purpose of this research is to examine how environmental committees, institutional shareholdings, and board independence affect managerial carbon disclosure decisions, particularly those of firms belonging to highly polluting industries. We focus on Italian firms that operate in a code law environment but that have the option either to adopt the unitary corporate structure prevalent in common law countries or to retain the dual corporate structure used in code law countries. We use weighted and unweighted carbon disclosure indexes based on the Kyoto Protocol requirements. The findings show that all factors greatly affect voluntary carbon disclosure and that their impact is especially strong for firms in highly polluting industries. This study has important implications for managers and regulators.